Histone isoforms and the oncohistone code. (April 2021) - Flaus, Andrew; Downs, Jessica A; Owen-Hughes, Tom
Abstract : Recent studies have highlighted the potential for missense mutations in histones to act as oncogenic drivers, leading to the term 'oncohistones'. While histone proteins are highly conserved, they are encoded by multigene families. There is heterogeneity among these genes at the level of the underlying sequence, the amino acid composition of the encoded histone isoform, and the expression levels. One question that arises, therefore, is whether all histone-encoding genes function equally as oncohistones. In this review, we consider this question and explore what this means in terms of the mechanisms by which oncohistones can exert their effects in chromatin.